Self-Efficiacy Siswa dalam Pembelajaran Matematika - Riri Ramadhani Fitri; Keysha Aurelia; Alya Devita Putri; Fathir Aziva Azra; Novferma Novferma; Husni Sabil (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2026)
Self-efficacy is an affective aspect that plays an important role in mathematics learning because it influences students' confidence in their ability to understand material, complete assignments, face learning difficulties, and achieve optimal learning outcomes. A good level of self-efficacy can encourage students to be more active, diligent, and confident during the learning process. However, differences in the level of self-confidence between students remain a factor that influences success in learning mathematics. This study aims to describe students' levels of self-efficacy in mathematics learning. The study used a descriptive quantitative method with 27 students as research subjects. The instrument used was a self-efficacy questionnaire consisting of 25 statements using a Likert scale with answer options: Very Appropriate (SS), Appropriate (S), Undecided (R), Not Appropriate (TS), and Very Not Appropriate (STS). The instrument was compiled based on six indicators, namely confidence in understanding mathematics material, confidence in completing assignments or problems, persistence in facing learning difficulties, confidence in asking questions and discussing, confidence in achieving good learning outcomes, and the ability to find solutions when experiencing difficulties in learning mathematics. Data were collected through questionnaires and analyzed using descriptive analysis based on the category of self-efficacy level. The results showed that 6 students (22.2%) were in the very high category, 16 students (59.3%) in the high category, and 5 students (18.5%) in the moderate category. These findings indicate that students generally have a high level of self-efficacy in learning mathematics. The implication of this research is the need for learning strategies that can maintain and increase student confidence and engagement in the mathematics learning process.